Produção de forrageiras cultivadas e conforto térmico em sistemas silvipastoris na caatinga - Santos Neto, Clemente Fernandes dos (2021)
The present thesis was composed of four chapters, the first: Forage production of tropical grasses in silvopastoral systems in a semiarid environment, the second chapter: Forage production and structural characteristics of forage palm in silvopastoral systems in a semiarid environment, the third: Diversity of plants and development of Cordia goeldiana in Caatinga grated in bands and preserved and the fourth: Microclimate and indices of thermal comfort in silvopastoral systems in a semiarid environment. In the first chapter, the physiology, the, structural characteristics and the production of Urochloa mosambicensis (current grass), Pennisetum ciliare (buffel grass) and Megathyrsus maximus (grass-massai) were subjected to different wood coverings with SS46 (silvipastoril system with 46,15% banded wood cover), SS30 (silvopastoral system with 30% banded wood cover) and SS18 (silvopastoral system with 17.64% banded wood cover). The experimental design was completely randomized with three replications in a split-plot scheme, with repeated measures over time (2018 and 2019). Photosynthetically active radiation on the leaf, photosynthetic rate, average canopy height, tiller population density and total forage biomass (BFT) were evaluated. The SS46 system promoted lesser leaf photosynthesis between Pennisetum ciliare and Urochloa mosambicensis. There was no difference in the leaf photosynthesis of Pennisetum ciliare and Urochloa mosambicensis in the SS18 and SS30 systems. SS46 favored lower DPP of grasses. The grasses showed the same DPP in the SS30 and SS18 systems. Grass BFT was lower in SS46 compared to SS30 and SS18. The silvopastoral systems SS30 and SS18 can be adopted without compromising the physiological characteristics of Urochloa mosambicensis and Pennisetum ciliare and the structural and productive characteristics of Urochloa mosambicensis, Megathyrsus maximus and Pennisetum ciliare. In the second chapter, the objective was to evaluate the productive characteristics of Opuntia stricta (Palma forage cv. Orelha de Elefante Mexicana) and Nopalea cochenillifera (Palma forage cv. Miúda) submitted to different wood coverings with SS46 (silvopastoral system with 46.15% coverage) woody strip), SS30 (silvopastoral system with 30% woody cover) and SS18 (silvopastoral system with 17.64% woody cover). The experimental design was completely randomized with three replications in a split-plot scheme. The average canopy height, number of cladodes per linear meter and total forage biomass (BFT) were evaluated, considering the east, center and west positions. A lower mean height of the canopy of Nopalea cochenillifera was observed in the east and west positions. Higher production of Nopalea cochenillifera and Opuntia stricta cladodes was found in the center position in the SS18 and SS30 systems. The Nopalea cochenillifera and Opuntia stricta cultivated in SS46 systems showed lower BFT in the center position. The silvopastoral systems SS30 and SS18 can be adopted without compromising the structural and productive characteristics of the palm Opuntia stricta and Nopalea cochenillifera. In the third chapter, the aim was to evaluate the diversity and tree development of an area of Caatinga vegetation thinned in strips compared to an area of preserved Caatinga vegetation. The treatments used were: thinned area in Caatinga strips and area of Caatinga vegetation preserved in secondary succession stage. The experimental design was completely randomized with repeated measures over time. Evaluations of: phytosociological survey of tree species, relative density, total height of the plant, diameter of the height of the base at 0.30 m from the soil, diameter of the height of the chest at 1.3 m from the soil were carried out. In the phytosociological survey, the species belonging to the Fabaceae family were very representative with the presence of 07 of the 12 identified species, in both areas of Caatinga, there was a predominance of the species Cordia goeldiana with 81.6% of relative density in the Caatinga, grated in bands and 79.17% in the preserved Caatinga. The mechanized thinning of the Caatinga in bands decreases the diversity of plants that have low relative density, without affecting the diameter and volume of Cordia goeldiana in the period of three years. In the fourth chapter, the objective was to evaluate the microclimate and indices of animal thermal comfort, in sun and shade, submitted to different wood coverings with SS46 (silvopastoral system with 46.15% woody cover in band), SS30 (silvopastoral system with 30% of woody cover in strip) and SS18 (silvopastoral system with 17.64% of woody cover in strip). The experimental design was completely randomized in a split plot scheme with repeated measures over time. The environmental variables, relative humidity (%), wind speed (m s-1), dry bulb temperature (° C), wet bulb temperature (° C), black globe temperature (° C) and temperature were collected for calculating the black globe temperature and humidity index (ITGU) and radiant thermal load (CTR). The SS46, SS30 and SS18 systems showed no differences between the black globe temperature and humidity index and the radiant thermal load in the sun position. There were significant reductions in the temperature index of black globe and humidity and the radiant thermal load inside the tree component promoting improvement in the thermal environment at times of higher radiation load.